Generation of 3D Skin Equivalents Fully Reconstituted from Human Induced Pluripotent Stem Cells (iPSCs) - Itoh, Munenari; Umegaki-Arao, Noriko; Guo, Zongyou; Liu, Liang; Higgins, Claire A.; Christiano, Angela M. (PLOS ONE, 2013)
Recent generation of patient-specific induced pluripotent stem cells (PS-iPSCs) provides significant advantages for cell- and gene-based therapy. Establishment of iPSC-based therapy for skin diseases requires efficient methodology for differentiating iPSCs into both keratinocytes and fibroblasts, the major cellular components of the skin, as well as the reconstruction of skin structures using these iPSC-derived skin components. We previously reported generation of keratinocytes from human iPSCs for use in the treatment of recessive dystrophic epidermolysis bullosa (RDEB) caused by mutations in the COL7A1 gene. Here, we developed a protocol for differentiating iPSCs into dermal fibroblasts, which also produce type VII collagen and therefore also have the potential to treat RDEB. Moreover, we generated in vitro 3D skin equivalents composed exclusively human iPSC-derived keratinocytes and fibroblasts for disease models and regenerative therapies for skin diseases, first demonstrating that iPSCs can provide the basis for modeling a human organ derived entirely from two different types of iPSC-derived cells.